1996
DOI: 10.1523/jneurosci.16-05-01679.1996
|View full text |Cite
|
Sign up to set email alerts
|

Retinal degeneration in transgenic mice with photoreceptor-specific expression of a dominant-negative fibroblast growth factor receptor

Abstract: Mutant cDNAs coding for dominant-negative forms of the fibroblast growth factor receptors 1 (FGFR-I) and 2 (FGFR-2) that lack tyrosine kinase activity were ligated to a 2.2 kb DNA fragment containing the bovine rhodopsin promoter and used to generate transgenic mice. Six independent lines were generated with the FGFR-1 construct, and five were generated with the FGFR-2 construct. Five of the six FGFR-1 mutant lines and all five FGFR-2 mutant lines showed transgene expression in the retina by reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 36 publications
4
56
1
Order By: Relevance
“…We showed that this mutant receptor inhibited activation of wild-type EphA receptors both in vitro and in transgenic mice. This finding is consistent with several previous studies that kinase-null mutant receptors inhibit activation of wild-type receptors both in vitro and in transgenic animals (32)(33)(34)(35)(36). The truncated receptor may inhibit endogenous receptor function by several potential mechanisms.…”
Section: Expression Of a Truncated Epha Receptor Alters Hippocampal Axonsupporting
confidence: 93%
“…We showed that this mutant receptor inhibited activation of wild-type EphA receptors both in vitro and in transgenic mice. This finding is consistent with several previous studies that kinase-null mutant receptors inhibit activation of wild-type receptors both in vitro and in transgenic animals (32)(33)(34)(35)(36). The truncated receptor may inhibit endogenous receptor function by several potential mechanisms.…”
Section: Expression Of a Truncated Epha Receptor Alters Hippocampal Axonsupporting
confidence: 93%
“…Meeson and R.A.L., unpublished), confirmation that growth factor deprivation-induced apoptosis is an important component of capillary regression awaits further experimentation. This mechanism is consistent with the emerging view that all cells are dependent on growth factors for their survival in vivo (Angeletti et al, 1971;Raff, 1992;Chow et al, 1995;Campochiaro et al, 1996) and in particular with the recent observation that endothelial cell growth factors have survival stimulating activity (Alon et al, 1995).…”
Section: Is Flow Stasis Required For Programmed Capillary Regression?supporting
confidence: 88%
“…The most likely explanation for this observation is that lens fiber cells are dependent upon FGF for their survival as well as for their differentiation (Chow et al, 1995;Robinson et al, 1995a). This would certainly be consistent with an expanding literature documenting the survival stimulating activity of a variety of growth factors in vitro and in vivo (Angeletti et al, 1971;Raff, 1992;Campochiaro et al, 1996).…”
Section: Growth Factor Signal Deprivation Induces Apoptosis Of Lens Fsupporting
confidence: 86%
“…It was shown that inhibition of the FGFR1-mediated pathway in Xenopus embryos resulted in a 50% loss of photoreceptor and amacrine cells, with a concomitant increase of Müller cells (McFarlane et al, 1998). The role of FGF signaling through receptors FGFR1 and FGFR2 in the survival of murine photoreceptor cells has also been investigated (Campochiaro et al, 1996). These authors demonstrated that inhibition of FGF signaling using ∆FGFR1 and ∆FGFR2 resulted in a progressive death of photoreceptor cells.…”
Section: Introductionmentioning
confidence: 99%